2010
DOI: 10.1074/jbc.m110.109207
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Is a Downstream Effector of AKT That Mediates Its Antiapoptotic Effects via Suppression of Fas Ligand

Abstract: MicroRNA-21 (miR-21) is highly up-regulated during hypertrophic and cancerous cell growth. In contrast, we found that it declines in cardiac myocytes upon exposure to hypoxia. Thus, the objective was to explore its role during hypoxia. We show that miR-21 not only regulates phosphatase and tensin homologue deleted on chromosome 10 (PTEN), but also targets Fas ligand (FasL). During prolonged hypoxia, down-regulation of miR-21 proved necessary and sufficient for enhancing expression of both proteins. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
216
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(225 citation statements)
references
References 47 publications
8
216
1
Order By: Relevance
“…As previously demonstrated, FasL is a target of miR-21 (Sayed, et al 2010). The connection between estrogen, miR-21 and FasL has previously been shown in bone in which, with the suppression of mir-21 expression, estrogen induces FasL production followed by osteoclastic apoptosis (Sugatani and Hruska.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As previously demonstrated, FasL is a target of miR-21 (Sayed, et al 2010). The connection between estrogen, miR-21 and FasL has previously been shown in bone in which, with the suppression of mir-21 expression, estrogen induces FasL production followed by osteoclastic apoptosis (Sugatani and Hruska.…”
Section: Discussionmentioning
confidence: 79%
“…According to Olivieri et al (2012b), plasma miR-21 levels showed age-related differences as well as variations between patients in relation to age-associated conditions, such as cardiovascular disease, and their agematched controls. Interestingly, miR-21 has been shown to regulate FasL expression (Sayed, et al 2010). MiR-146a is strongly associated with inflammation and its expression is NF-κB-dependent and it has been proposed to play an important role in the regulation of innate immune response by regulating the production of cytokines such as IL1-beta (IL-1β) and TNF-α (Taganov, et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-21 mediated anti-apoptotic effects of Akt by direct suppression of mRNA expression of Fas ligand (Fasl), and transgenic overexpression of miR-21 reduced infarct size in a murine model of ischemia/reperfusion. 32) In addition, miR-214 protected the murine hearts against ischemia/reperfusion injury by direct suppression of mRNA expression of sodium/calcium exchanger 1 (Scl8a1), a key regulator of Ca 2+ influx. 33) Conversely, miR-25 suppressed mRNA expression of sarcoplasmic reticulum Ca 2+ uptake pump (Atp2a2), and inhibition of miR-25 by injection of antisense oligonucleotide (antagomiR) improved cardiac function and survival in a murine model of heart failure induced by transverse aortic constriction.…”
Section: Article P422mentioning
confidence: 99%
“…Reciprocally, Akt-inducing upregulation of miRNA-21 inhibits PTEN. 64,82 Hwang et al reported that lower than median miRNA-21 expression was correlated to longer overall as well as diseasefree survival and benefit from adjuvant gemcitabine treatment in two independent cohorts of 82 Korean and 45 Italian PC cases. Furthermore, transfection with anti-miRNA-21 enhanced the chemosensitivity of PC cells.…”
Section: Micrornas As Epigenetic Targetsmentioning
confidence: 99%